1996
DOI: 10.1093/nar/24.22.4487
|View full text |Cite
|
Sign up to set email alerts
|

DNA Binding of Jun and Fos bZip Domains: Homodimers and Heterodimers Induce a DNA Conformational Change in Solution

Abstract: We constructed plasmids encoding the sequences for the bZip modules of c-Jun and c-Fos which could then be expressed as soluble proteins in Escherichia coli. The purified bZip modules were tested for their binding capacities of synthetic oligonucleotides containing either TRE or CRE recognition sites in electrophoretic mobility shift assays and circular dichroism (CD). Electrophoretic mobility shift assays showed that bZip Jun homodimers and bZip Jun/Fos heterodimers bind a collagenase-like TRE (CTGACTCAT) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
18
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 25 publications
10
18
0
1
Order By: Relevance
“…The K d of Fos homodimers in HeLa cells was 6.7 Ϯ 1.7 M, which is on the same order of magnitude as the value of 5.6 M determined for its isolated leucine zippers in vitro by circular dichroism (14). Values reported for the heterodimers of the isolated leucine zippers (10,48,49) or longer polypeptides (50) in vitro varied between 1 and 140 nM. For the Fos-Jun heterodimer, we found a K d range of 10 to 370 nM in live cells, which depended on the Fos/Jun ratio and on putting the donor and acceptor tags on one or the other protein.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The K d of Fos homodimers in HeLa cells was 6.7 Ϯ 1.7 M, which is on the same order of magnitude as the value of 5.6 M determined for its isolated leucine zippers in vitro by circular dichroism (14). Values reported for the heterodimers of the isolated leucine zippers (10,48,49) or longer polypeptides (50) in vitro varied between 1 and 140 nM. For the Fos-Jun heterodimer, we found a K d range of 10 to 370 nM in live cells, which depended on the Fos/Jun ratio and on putting the donor and acceptor tags on one or the other protein.…”
Section: Discussionsupporting
confidence: 68%
“…In addition to forming stable heterodimers with c-Fos (7-9), c-Jun can also homodimerize, as revealed in vitro by electrophoretic mobility shift assay (EMSA) (8), and bind to DNA as a homodimer, although with lower affinity than the heterodimer (8,10). In contrast, the c-Fos homodimer was found to be unstable in vitro, and thus, c-Fos has been thought to interact with DNA only by forming heterodimers with c-Jun (9,11,12).…”
mentioning
confidence: 99%
“…Indeed, the c-Jun RhG /c-Jun Cy5 interactions both with and without non-labeled AP-1 oligonucleotide could be detected in this study, whereas the interaction among c-Jun RhG /Cy5-labeled AP-1/non-labeled Jun was not detected in the previous study (11). The apparent K d of c-Fos/c-Jun/AP-1 found in this study was in good agreement with reported values (25,26). The K d of c-Jun homodimer and AP-1 sequence also coincided with the value of 140 nM determined previously (25).…”
Section: Discussionsupporting
confidence: 93%
“…As shown in Figure 5C, only the Fos-Jun-DNA complex molecule carrying both RhG and Cy5 was observed in the cross-correlation and quantified, but not the Fos-Fos and Jun-Jun pairs. The apparent dissociation constant K d for the binding of the Fos-Jun heterodimer to DNA can be obtained from a single FCCS measurement (Földes-Papp and Kinjo 2001; Jankowski and Janka 2001): The K d value was found to be 30 nM (see supplemental data on the web site), which is consistent with a value of 50 nM independently derived from the results of gel shift assay (John et al 1996).…”
Section: Genome Research 489supporting
confidence: 72%